2015
DOI: 10.1016/j.jvs.2013.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Tibial osteochondroma inducing popliteal artery compression

Abstract: Compression of the neurovascular contents of the popliteal fossa is a rare condition that leads to exercise-induced pain and paresthesias in young athletes. Most frequently, it is caused by musculotendinous abnormalities resulting in popliteal entrapment syndrome. Bony abnormalities rarely are implicated but can produce symptoms that mimic popliteal entrapment syndrome. We present a patient with a tibial metaphysis osteochondroma inducing popliteal artery compression that was relieved after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Eschelman et al reported that among 56 cases of osteochondromas with vascular involvement, only six were tibial and only half of these caused arterial compression, as observed in our patient 9 .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Eschelman et al reported that among 56 cases of osteochondromas with vascular involvement, only six were tibial and only half of these caused arterial compression, as observed in our patient 9 .…”
Section: Discussionsupporting
confidence: 67%
“…In 2013, Henry et al 9 reported a case of intermittent claudication in a 23-year-old woman with a solitary tibial osteochondroma, which was treated by division of the soleus muscle and resection of the osteochondroma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple studies have looked at vascular complications from osteochondromas, including intermittent compression, pseudoaneurysm, thrombosis, distal emboli, and venous thrombosis or compression. 1 , 2 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Enlargement of the osteochondroma can lead to compression of the vascular structures, leading to arterial or venous thrombus with subsequent distal embolization. Eschelman et al 7 found that 68% of vascular injuries were pseudoaneurysms secondary to what has been proposed as the osteochondroma's cartilaginous cap ossifying and then the pulsatile nature of the artery rubbing against it, causing damage.…”
Section: Discussionmentioning
confidence: 99%
“…As osteochondroma manifests as a solitary lesion or as a component of numerous osteochondromas with multiple hereditary exostoses, it is posited that osteochondroma is a developmental lesion engendered from cellular segregation of epiphyseal growth plate [5,6]. As osteochondroma develops from displaced cartilage cells constituting growth plates, it is hypothesized that endochondral ossification of articulated bone may configure an osteochondroma.…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…Possibly, a fragment of growth plate herniates through the periosteum which evolves perpetually with consequent emergence of a sessile or pedunculated lesion, commonly within the metaphyseal region. Detached fragment of growth plate can spontaneously appear as primary osteochondroma or a secondary osteochondroma may emerge because of irradiation, surgical intervention, or fracture [5,6].…”
Section: Disease Pathogenesismentioning
confidence: 99%